A SNP in PLAG1 is associated with body height trait in Chinese cattle. (23rd October 2019) - Hou, J.; Qu, K.; Jia, P.; Hanif, Q.; Zhang, J.; Chen, N.; Dang, R.; Chen, H.; Huang, B.; Lei, C.
Summary: Stature is an important quantitative trait for cattle performance, which influences herd productivity. Previous studies have reported that an SNP (AC_000171.1:g.25015640G>T, rs109815800) in Pleomorphic adenoma gene 1 ( PLAG1 ) on chromosome 14 (CHR14) is associated with bovine stature. To validate whether rs109815800 is associated with the body height of Chinese cattle, we carried out an association analysis using 558 adult cattle samples from seven populations. Then, 1038 samples from 38 Chinese cattle breeds were used to show the geographical distribution of this variant in China. The results showed that the Q allele (G allele) increased the height of cattle. Furthermore, the frequencies of Q allele in Chinese native breeds tend to decrease from northern China to southern China, and the frequency of Q allele in two Chinese beef cattle breeds is much higher than that in another 36 Chinese local cattle breeds. Our data suggest that the prevalence of the Q allele is correlated with latitude in China.